2009
DOI: 10.1111/j.1948-7134.2009.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics of Anopheles spp. (Diptera: Culicidae) in a malaria endemic region of Sukabumi, West Java, Indonesia

Abstract: A 15-month bionomic study of Anopheles species was conducted in two ecologically distinct villages (coastal and upland) of Sukabumi District, West Java, Indonesia from June 2006 to September 2007. Mosquitoes were captured using human-landing collections at both sites. During the study, a total of 17,100 Anopheles mosquitoes comprising 13 Anopheles species were caught: 9,151 at the coastal site and 7,949 at the upland site. Anopheles barbirostris, Anopheles maculatus, and Anopheles vagus were the predominant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…An. aconitus is also considered a species that breeds at high altitudes [43]. In the present study, both these species were found at study sites with highest elevations: An.…”
Section: Discussionmentioning
confidence: 49%
“…An. aconitus is also considered a species that breeds at high altitudes [43]. In the present study, both these species were found at study sites with highest elevations: An.…”
Section: Discussionmentioning
confidence: 49%
“…Larvae are frequently found in open country near foothills and forest fringes with rice fields (active and fallow), various shallow pools (rock, stream, seepage, flood) and slow moving streams [154,158] with grassy margins (Tables 7, 9). Both coastal plain and upland rice fields (young and older plants) are particularly favoured habitats [37,161,163,169,174,182,186,187], especially when plants are closer to maturity and greater than 1.5 m in height [127,163,188]. Larvae can also be found in abundance in fallow rice fields and rain-fed pools in dry fields (Tables 7, 9).…”
Section: Resultsmentioning
confidence: 99%
“…bovids) are the commonly preferred hosts, when they are scarce, they will feed on humans as an alternative host [10,180-182] (Table 11). Females will feed on humans both inside and outside houses and in varying proportions, depending on location, generally with no strong preference reported [100,175,187]. Feeding can occur throughout the evening, typically beginning at dusk [100,176], with the majority of females feeding on humans before midnight [161,179,192,193] (Table 11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations